Synergistic endocrine disruption and cellular toxicity of polyethylene microplastics and bisphenol A in MLTC-1 cells and zebrafish - Ting Ye; Ruiquan Yang; Shumao He; Jiahui Li; Yi Liu; Can Li; Heng Luo (Scientific Reports)
Abstract The study investigates the synergistic endocrine disruption and cellular toxicity resulting from co-exposure to polyethylene microplastics (PE-MPs) and bisphenol A (BPA) in zebrafish and MLTC-1 cells. Previous research has extensively examined the individual effects of PE-MPs and BPA on endocrine systems and cellular health. However, the specific interactions and combined toxicological impacts of these two common environmental pollutants remain underexplored, particularly in terms of their synergistic effects on endocrine pathways and cellular viability. To fill this knowledge gap, we characterized PE-MPs using scanning electron microscopy and Raman spectrometry and exposed MLTC-1 cells to PE-MPs, BPA, or combinations of both. The results showed that co-exposure to 100 µg/mL PE-MPs and 100–150 µmol/L BPA for 48 h significantly decreased cell viability, increased apoptosis rates, induced G2/M cell cycle arrest, reduced mitochondrial membrane potential, and altered the transcriptional expression of genes related to steroidogenesis. Specifically, co-exposure upregulated the Ar while downregulating Lhr and 3β-Hsd, with these effects being more pronounced than those observed with single exposures. In a complementary in vivo study, adult zebrafish were exposed to environmentally relevant concentrations of PE-MPs (1 mg/L) and BPA (1.5 µg/L) for 28 days. This co-exposure resulted in significant increases in the GSI and alterations in the gene expression associated with the HPG axis. In male zebrafish brains, genes such as Gnrh2, Esr1, and Ar were downregulated, while in female brains, Gnrh3, Esr1, and Ar also exhibited downregulation. In male testes, Star, Cyp11a1, and Hsd11b2 were upregulated, whereas Cyp19a1a, Hsd3b, Hsd20b, and Hsd17b3 were downregulated. In contrast, female ovaries showed upregulation of Cyp11a1, Cyp17, Cyp11b, Hsd3b, Hsd20b, and Hsd17b3, while Cyp19a1a was downregulated, indicating a sex-specific endocrine disruption. Overall, the findings reveal that co-exposure to PE-MPs and BPA induces synergistic toxic effects both in vitro and in vivo, which underscores the importance of studying the effects of combined pollutants to better assess environmental health risks.